Key informant analysis for climate smart agriculture practices in Tra Hat Village, Vietnam - Ngo Dang Phong; Le Minh Duong; Tran Nhat Lam Duyen; Wassmann, Reiner; Sander, Björn Ole (2019)
This paper presents the results of key informant interviews conducted in Tra Hat Climate-Smart Village (CSV) in Vietnam. The interviews aimed to further assess the climate-smart agriculture (CSA) practices that farmers wanted to adopt on their farms, as well as the factors and barriers for adoption. Results of the household surveys conducted in Tra Hat CSV were considered on this paper as well. Altogether, the results of the interviews and surveys would serve as a guide to implement the prioritized CSA practices and out-scale them in Bac Lieu Province. Majority of key informants stated that rice production must be prioritized because it is the main livelihood of farmers in Tra Hat CSV. Rice production could be complemented with animal husbandry, provided that its market is stable and the focus points on sanitation treatment. Home gardens emerged as another CSA practice that farmers preferred on their farms. Farmers considered economic and environmental benefits for prioritizing these CSA practices. In contrast, farmers did not prioritize leaf color charts and salt-tolerant rice varieties for their perceived unsuitability in their village. In terms of CSA technologies, farmers expressed their willingness to undergo trainings and attend demonstration trials to learn them. The technologies and practices prioritized by the farmers can be integrated into a CSA portfolio to foster farmer uptake and adoption. Participation of local government authorities, farmer cooperatives, and the private sector could then boost the portfolio’s scaling potential.